EduPMO: a Framework for Multimedia Production Management - Amorim, Joni A.; Miskulin, Rosana G. S. [UNESP]; Miskulin, Mauro S.; Informat Resources Management Assoc (Igi Global, 2013)
Engineering is seen today as a synonym of innovation, especially for providing technological solutions that affect not only daily work and entertainment, but education as well. Project portfolio management of multimedia production and use emerges today as a challenge both for the enrichment of traditional classroom based teaching and for distance education offering. In this way, this chapter intends to answer the following question: Which are the fundamental aspects to be considered in the management of projects on educational multimedia production and use? This research presents a proposal of a project management model for digital content production and use. The model, the methodology and the implementation will be named EduPMO, an abbreviation of Educational Project Management Office. Therefore, the model, the methodology, and the implementation should be understood as related but independent entities. This interdisciplinary investigation involves different topics, going from metadata and interoperability to intellectual property and process improvement.